Молоді фахівці – майбутнє науки. Вип. 16 : збірник наукових праць студентів (з нагоди 220-річчя від дня заснування Харківського національного університету імені В. Н. Каразіна) [Електронний ресурс] - (:unkn) unknown (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Збірник присвячено дослідженню проблем семантичних та прагматичних аспектів тексту і дискурсу, лінгвокультурології, навчання іноземних мов у закладах загальної середньої та вищої освіти. Матеріалом дослідження є сучасні європейські мови.

The collection is devoted to the study of issues regarding semantic and pragmatic aspects of text and discourse, linguistic and cultural studies, foreign language instruction in institutions of secondary and higher education. The research is based on contemporary European languages.
Young professionals – the future of science. Iss. 16 : a collection of students’ scholarly works dedicated to the 220 anniversary of V. N. Karazin Kharkiv national university [Electronic resource]
Keywords: HUMANITIES and RELIGION::Languages and linguistics; SOCIAL SCIENCES::Social sciences::Education::Subject didactics; SOCIAL SCIENCES::Other social sciences::Mass communication; SOCIAL SCIENCES::Other social sciences::Media and communication studies; гендер; дискурс; дискурсивна особистість; еколінгвістика; ідіостиль; інтерактивне навчання; комунікативна стратегія; концепт; лінгвокультурний типаж; мала проза; методи викладання; мультимодальність; невербальна комунікація; ономастика; стратегії й тактики; структурно-семантичний аналіз; технології навчання; художній простір; artistic space; communicative strategy; concept; discourse; discursive personality; ecolinguistics; gender; idiostyle; interactive teaching; learning technologies; linguocultural type; methods of teaching; multimodality; non-verbal communication; onomastics; short prose; strategies and tactics; structural and semantic analysis